Economics of Maize (Zea mays L.) and Soybean (Glycine max (L.) Merrill) Intercropping - Kithan, Lowrence; Longkumer, L. Tongpang (International Journal of Bio-resource and Stress Management, 2017)
A study was conducted during kharif,2015 at the experimental farm of School of Agricultural Sciences and Rural Development (SASRD) Nagaland University, Medziphema Campus, Nagaland under rainfed condition. The treatments comprised of different row ratios i.e. (1:1), (1:2), (2:1), (2:2) and (2:3) respectively of maize (Var. Dekalb All-Rounder) intercropped with soybean (Var. JSS-335) along with sole crops of maize and soybean. The experiment was laid in RBD with 4 replications and 7 treatments. Both maize and soybean as sole crops performed better in respect of growth characters such as plant height (cm), number of leaves plant-1,number of root nodules plant-1, root length (cm), and yield attributing characters viz.,cob weight (g), cob length (cm), number of pods plant-1, grain yield (26.99 q ha-1 ), seed yield (21.75 q ha-1) and B: C (0.85, 1.63) than in intercropping systems. Among the intercropping systems, paired rows (2:2) ratio of maize and soybean proved superior to all other treatments in respect of growth and yield attributing characters, grain yield of maize (23.08 q ha-1), seed yield of soybean (20.34 q ha-1), Gross return (` 100256), Net return (` 75472), LER (1.80) and B:C ratio (3.04). In a nutshell, based on the value of growth functions and yield attributing characters, paired (2:2) rows of maize and soybean was found to be biologically efficient system. As on economic indices of land equivalent ratio the system paired rows (2:2) was found to be economically profitable system for kharif seasons under rainfed season in Nagaland.